2001
DOI: 10.2166/wst.2001.0667
|View full text |Cite
|
Sign up to set email alerts
|

Potential and limitations of alum or zeolite addition to improve the performance of a submerged membrane bioreactor

Abstract: In this study, alum and natural zeolite were added to a submerged membrane bioreactor (MBR) not only to reduce membrane fouling but also to increase the removal of nitrogen and phosphorus. Alum addition reduced significantly the rising rate of suction pressure and also resulted in stable and better COD removal. Although phosphorus removal was more than 90% by chemical precipitation, nitrification inhibition was observed. With the addition of natural zeolite, membrane permeability was greatly enhanced by the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 0 publications
1
46
0
Order By: Relevance
“…For the alum dosage 59.18 mg/L it was 84~82% from then it was decreased in a step wise manner for successive higher dosage and it fell to a value of 74~76% for the alum dosage (97.13 mg/L). Lee et al [22] have used alum in the MBR reactor to improve its performance and found out that the addition of alum significantly reduced the suction pressure of the membrane but increased the effluent nitrogen level. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For the alum dosage 59.18 mg/L it was 84~82% from then it was decreased in a step wise manner for successive higher dosage and it fell to a value of 74~76% for the alum dosage (97.13 mg/L). Lee et al [22] have used alum in the MBR reactor to improve its performance and found out that the addition of alum significantly reduced the suction pressure of the membrane but increased the effluent nitrogen level. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 Reactor. This indicated that adding Fe(OH) 3 to SMBR could mitigate the membrane fouling effectively.…”
Section: Mixed Liquor Filterabilitymentioning
confidence: 89%
“…The membrane fouling causes permeating flux decline, requiring frequent membrane cleaning and even replacing, which increases the maintenance and operating costs of SMBR. Many attempts such as intermittent operation, jet aeration, air and water backwashing, dosing zeolite, O 3 , alum or powder activated carbon have been employed to reduce the membrane fouling [1][2][3][4]. However, membrane fouling in SMBR is still one of the major drawbacks for their wide application.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations